Artificial selection of insecticide resistance to lambda-cyhalothrin in Aedes aegypti and cross resistance to other insecticides - CHAVERRA-RODRÍGUEZ, DUVERNEY; CHAVERRA-RODRÍGUEZ, DUVERNEY; JARAMILLO-OCAMPO, NICOLÁS; FONSECA-GONZÁLEZ, IDALYD (Revista Colombiana de Entomología, 2012)
Aedes aegypti is the main vector of dengue virus worldwide. The chemical control of larvae and adults is based principally on organophosphate and pyrethroid insecticides, for which resistance has developed in the field. The management of resistance requires evaluating how rapidly it can develop and the possible generation of cross-resistance between both groups of insecticides. This study evaluates the effects of selection on Ae. aegypti with lambda-cyhalothrin on the development of resistance to this pyrethroid over seven generations and its impact on the appearance of cross-resistance to temephos, malathion, and permethrin insecticides under laboratory conditions. Adults were obtained from larvae collected in the field in Cúcuta (Colombia) and the descendants were exposed to gradually increasing concentrations of insecticides each generation. The development of resistance was confirmed using bioassays on the larvae and adults. Selection increased the ratio of resistance (RR) in each generation (1.25X average). At generation F7, the population was highly resistant to lambda-cyhalothrin for both adults (100% mortality in F1 decreased to 35% mortality in F7) and larvae (RR50 F1 = 24.22 X, RR50 F7 = 61.52 X) when compared to the susceptibility of Rockefeller, the reference line. The line resistant to lambda-cyhalothrin did not present cross-resistance to temephos and malathion (organophosphates) but did present resistance to permethrin (pyrethroid). The information obtained suggests that the rotation of organophosphates and pyrethroids continues to be an appropriate alternative for managing the appearance of resistance on dengue control strategies.